Application of tuned-mass system on railway catenary to improve dynamic performance. (15th June 2018) - Liu, Zhendong; Stichel, Sebastian; Rønnquist, Anders
Highlights: Proposing a method to improve the dynamic performance of railway catenary system. Studying the influence of lumped-mass and tuned-mass on the pantograph-catenary interaction. Studying the dynamic behaviour of the additional local-DOF-system on the catenary system. Suggesting a possible way to implement the tuned-mass system on the existing catenary. Abstract: Finding a simple and practical method to improve the dynamic behaviour of a specific structure is always desirable in civil and mechanical engineering. The railway catenary system is the overhead power line above the track, interacting together with the train-based pantograph to transfer electric power. Due to vertical stiffness variation and a propagating wave along the catenary, the fluctuation of the contact force becomes significant with operational speed increasing. Therefore, this has become one of the key factors which limits the operational speed and service life of key components. Wire misalignment, structural errors and uneven mass distribution of the catenary can further deteriorate the contact stability. In order to achieve a higher speed on existing lines, the catenary needs large-scale modification implying long out-off-service time. From the designing aspect, all components directly fixed to the catenary, like clamps, steady arms and other fittings, are made as light and small as possible to minimize disturbances. However, in other engineering applications, some well-designed additional mass systems are adopted aiming to improve their dynamic performance. In order to take advantage of these unavoidable masses on the catenary, an investigation on lumped-mass distribution in single-pantograph and multi-pantograph operations is performed with help of a 3D pantograph-catenary finite element (FE) model. The results show that a rightly-tuned mass, here the implementing location and the elasticity of its connection, can positively change the dynamic performance without implementing large-scale modification to the existing system. Through a brief discussion on the mechanism of this positive effect, this paper proposes that applying some artificial tuned-mass system can be a possible method to overcome unfavourable working conditions or even allow speed increase on existing lines.